CHATBOT BASED STUDENT INFORMATION SYSTEM (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The mission of the Student Information Management system is to create an integrated information technology environment for students. Our goal is to focus on services and integration for end users.It is an Android based self-service environment for students, prospective students, and employees; an administrative transaction processing environment for  early admissions; an informative environment for all levels of faculty and staff to do reporting, data extraction and information analysis.It is mainly useful for educational establishments to manage student data which also facilitates all individual associated information for easier navigation on daily basis. It provides capabilities for entering student test and other assessment scores, building student schedules, tracking student attendance and managing many other student-related data needs in a college.Our easy-to-use, integrated college administration application would be used to reduce time spent on administrative tasks, as to concentrate on other skillful practical activities other than book worming.